2001
DOI: 10.1038/sj.sc.3101220
|View full text |Cite
|
Sign up to set email alerts
|

Human spinal cord injury: new and emerging approaches to treatment

Abstract: The World Health Organization together with the Iceland Ministry of Health and Social Security sponsored a conference entitled 'Human Spinal Cord Injury: New and Emerging Approaches to Treatment' held on May 31-June 2, 2001 in Reykjavik, Iceland. To help catalyze the development of new paradigms to address spinal cord injury, the conference's overall goal was to bring in a diversity of perspectives, ranging from state-of-the-art stem cell biology to the ancient wisdom of Eastern Medicine. The purpose of this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…6,7,20,27,30 There are several recent reports of successful somatic nerve transfers in animal models and in patients for restoration of bladder function. 3,4,9,10,14,19-22,26,31 We found, using a canine model, that bladder reinnervation after sacral ventral root transection can be achieved by nerve transfer and surgical coaptation of coccygeal roots to the severed sacral roots, or transfer of genitofemoral nerves to the pelvic nerve as evidenced by increased bladder pressure upon functional electrical stimulation of these nerves after time had elapsed for reinnervation. In the majority of animals in each group, effective detrusor contractions were elicited with stimulation of the reinnervated pelvic nerve.…”
Section: Introductionmentioning
confidence: 85%
“…6,7,20,27,30 There are several recent reports of successful somatic nerve transfers in animal models and in patients for restoration of bladder function. 3,4,9,10,14,19-22,26,31 We found, using a canine model, that bladder reinnervation after sacral ventral root transection can be achieved by nerve transfer and surgical coaptation of coccygeal roots to the severed sacral roots, or transfer of genitofemoral nerves to the pelvic nerve as evidenced by increased bladder pressure upon functional electrical stimulation of these nerves after time had elapsed for reinnervation. In the majority of animals in each group, effective detrusor contractions were elicited with stimulation of the reinnervated pelvic nerve.…”
Section: Introductionmentioning
confidence: 85%
“…4,5,9,14,21,23,24 There are recent reports of successful somatic nerve transfers, in animal models and in patients, for restoration of bladder function. 8,10,13,1517,24,25 Using a canine model, we have shown that bladder reinnervation after sacral ventral root transection can be achieved through nerve transfer and surgical coaptation of coccygeal roots to the severed sacral roots, or transfer of the genitofemoral nerve to the pelvic nerve, as evidenced by increased bladder pressure on functional electrical stimulation. 1517 Effective detrusor contractions were elicited with stimulation of the reinnervated pelvic nerve.…”
mentioning
confidence: 98%
“…Therefore, it complements the spinal tissue restructuring. In a paradigm-expanding assumption, we believe that the nerve impulse may be mediated either through a biochemical conduction using neurotransmitters or through electromagnetic channels using a wavelength (14,13,14).…”
Section: Resultsmentioning
confidence: 99%